Planning with self‑organised initiatives: from fragmentation to resilience - Moreno Pessôa, Igor Tempels (A+BE | Architecture and the Built Environment, 2019)
Over the last half century, the Global South has faced a strong rise in the rate of urbanisation. Although this process differs from region to region, rapid urbanisation has created many challenges for countries in the Global South. Brazil is no different. The largest country in South America has jumped from an urban population of 44.67% in 1960 to 84.36% in 2010, according to the Brazilian Institute of Geography and Statistics (IBGE, 2018). While urban growth is relatively stable in Brazil today, the challenges that came with the rapid increase will be felt for many years to come. One of the main challenges was created due to this urban growth not being organised. The main growth in the cities was due to an opportunity-led development, which produced an extremely unequal urban fabric with spatial discontinuities and left-over spaces. Planning institutions have attempted to overcome this spatial fragmentation problem, but have faced many difficulties. This thesis demonstrates that spatial fragmentation in Brazilian metropolises is not only related to spatial discontinuities, but also to socioeconomic inequalities. This means that the physical connection between disconnected spaces does not necessarily create social connections between segregated groups. Walls in Brazil are not only physical but also social. This thesis investigates self-organised initiatives as possible entities to dismantle these invisible walls. Such initiatives help to create social connections between highly diverse groups in the public spaces of cities which have a high level of socioeconomic inequality. The cases of São Paulo, Rio de Janeiro and Brasília reveal a growth in the integration level from functional to symbolic, and even to community level in areas where these self-organised initiatives have been active. This increase in social connection between highly diverse groups has a positive impact on the resilience capacity of the urban system, improving the capacity for closer cooperation in the face of unexpected change. The thesis begins by analysing the spatial fragmentation of Brazilian metropolises and how this relates to resilience. Chapter 2 develops the concept of ‘porosity’ as a metaphor for these spatial discontinuities in the Brazilian metropolitan context. Data from IBGE was used to create a porosity index and generate a comparative perspective on all of the Brazilian metropolises. The index reveals that cities have very different factors composing their porosity, which in turn create different threats and opportunities regarding the resilience capacity of each city. Certainly, it is important to recognise the particularities of each context, and in this way the porosity index provides a starting point for understanding the spatial fragmentation occurring within Brazilian metropolises. Chapter 3 focuses on the two metropolises with the highest porosity index, Belém and Manaus, to examine how urban policies may affect their spatial fragmentation. The thesis uses the federal government’s Minha Casa, Minha Vida (MCMV) social housing programme to investigate the relationship between such programmes and spatial fragmentation. Using GIS-generated maps, it was possible to visualise the pattern of each case of fragmentation and overlap these with the location of the developments in the MCMV programme. The chapter reveals that despite reducing the housing deficit for the low-income segment, the MCMV programme is having a strong negative impact by raising the level of spatial fragmentation already present in both metropolises. In Chapters 4 and 5, the relationship between spatial fragmentation and self-organised initiatives is analysed. Using cases from São Paulo, Chapter 4 investigates how spatial fragmentation is influencing the work of such self-organised initiatives. It shows that the spatial fragmentation of São Paulo has a strong polarised structure, with the city centre as the main pole. Fragmentation in São Paulo is based on a dichotomy between centre and periphery that also influences where self-organised initiatives operate. Nevertheless, as Chapter 5 demonstrates, the initiatives studied are able to integrate people from extremely diverse socioeconomic contexts, even when being limited by spatial fragmentation. This social disconnection in contexts of inequality is one of the underlying forces driving spatial fragmentation in Brazil. In this sense, this integration capacity of self-organised initiatives is an important resource to tackle fragmentation in Brazilian metropolises and has been attracting the interest of urban planners. While there is a lot of potential for self-organised initiatives to be integrated into planning strategies in Brazilian metropolises, this is still not being explored by public authorities in the cities studied. The interaction between self-organised initiatives and public institutions is generally problematic and conflictual, despite the participation of some public servants in these initiatives. Much can be done to improve the relationship between self-organised initiatives and public authorities, and this conclusion led to the key recommendations of this investigation. The thesis also points to the active participation of urban planners in these initiatives, with even those who perform technical functions in public institutions becoming active. The results of Chapter 5 show that planners demonstrate a strong belief in the work of self-organised initiatives and their positive impact. Their engagement calls for further examination of the role of planners in such initiatives and their impact in other areas beyond spatial fragmentation. Despite being scientifically well grounded and having societal relevance, doctoral theses are frequently forgotten in the repositories of universities. With this in mind, this thesis aimed to not only be scientifically sound but to also have a strong societal impact. In addition to publishing articles as part of the thesis, I also explored other methods to improve its societal impact, making the research available on two open online platforms: the Global Urban Lab and the Rethink the City MOOC. The former aims to synthesise the findings and discussions of research in a manner accessible to the general public, while the latter aims to apply the research in planning education. Education can be an efficient tool to generate societal impact based on doctoral research, especially if connected to a massive educational tool such as a MOOC. The Rethink the City MOOC is presented here as a case study on how to generate societal impact by combining doctoral research and online education. The challenges and process of developing the Rethink the City MOOC are discussed in Chapter 6, which also presents some of the satisfactory results from the course, with 17,278 participants registering for the first two editions. This experience demonstrates how much impact doctoral research can have when aligned with online education.